Pedagogia do Futebol Americano nas aulas de Educação Física escolar: algumas contribuições à formação crítico-reflexiva no PIBID/UFLA (2020-2022) - Santos, Andreolle Augusto dos (2022)
In school physical education there is a historical context, in which there is little diversification of the contents covered. In view of this, there is a great predominance in the teaching of traditional sports in classes, namely: football, handball, volleyball and basketball - what we call the "fantastic quartet". Therefore, the objective of this research was to know what are the possible contributions that a course on American Football can add to the critical-reflexive training of the participants of PIBID - Physical Education at the Federal University of Lavras. For this, we use the concepts related to the pedagogy of sport, which seeks to plan, organize, systematize, execute and evaluate the processes of intervention, teaching and experience of Football in/from school. In addition, this course addressed other issues that cross pedagogical practice, such as history, ethnic-racial and gender problematizations, in order to offer possibilities for teaching this sport at school. Subsequently, we qualitatively analyzed the empirical materials produced in the course with the participants, which were obtained through written activities, narratives and other observations. As a result, we could observe a positive contribution in the training of teachers, presenting the football, breaking possible prejudices regarding its practice at school. In this way, allowing them to work this sport in a significant way in their teaching practice, expanding their training territories.